Globalization and Welfare State: The effect on Health Systems - Papaelias, Theodore (SPOUDAI Journal of Economics and Business, 2011)
The appearance of the national state is the most important event in the passage from the Middle to the New Ages. The rapid growth of commerce and cities strengthens the exchanges between different regions of Europe, primarily, and the rest of the world, secondly. The cottage industry transforms into handicraft and that into manufacture. The industrial revolution in the 18th - 19th century creates an intense social issue. The consequence is the emersion of the welfare state since the early 1880. After the 1929-33 crisis, the state intervention enforces the welfare state as the dominant regime throughout Western Europe, and establishes a standard for many countries. After the oil crises in 1973 and 1979 and the rise of liberalism, the welfare state confronts a sharp criticism. The fall of existing (real) socialism accelerates the evolutions and the prevalence of globalization leads to its decline. Health systems are the main, perhaps, expression of the welfare state. The paradigms of Bismarck and Beveridge dominate in most countries of the world (whereas, the liberal model in the U.S.A.). The expenditure on health amounts already to 9% or more of GDP, in 1980. But after this decade, a decrease begins, particularly in the public shareholding. This decay leads to a continuous reduction of public expenditure and to the increase of private insurance. The health systems, for a variety of reasons (adverse demographic evolutions, decline in income share of Europe in world GDP, etc.), will suffer eclipse. JEL Classifications: I10, I30